PENGARUH GAYA KEPEMIMPINAN “SUPORTIF” TERHADAP KEPUASAN KERJA MELALUI MOTIVASI KERJA DAN KINERJA GURU SEBAGAI VARIABEL MEDIASI (Studi Pada Guru TK se-kecamatan Slawi Kabupaten Tegal) - Rahayu, Sri; Kusmanto, Ary (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Leadership can be said to be a leader's way of directing, encouraging and managing all elements within an organization to realize a goal to be achieved, thereby producing maximum employee performance. To achieve this goal, efforts must be made to find out how a leader can encourage employee morale, so that the goals and objectives planned together can achieve the target. Apart from that, leaders can provide promotions for employees who excel in order to create employee job satisfaction. This research is related to the decreasing awareness of employees in terms of discipline, employee performance and decreasing work results which is possible as a result of a supportive leadership style, but as time goes by, this leadership style makes employees more relaxed, more free to do things outside the main work context. , thus causing problems to arise such as late work deadlines. This research was conducted on kindergarten teachers in Slawi sub-district, Tegal district with a total of 100 respondents using a questionnaire on the Googleform application. The research method used is quantitative with the SmartPLS 3.0 data analysis tool. The results obtained are based on the data analysis and discussion described, this research concludes that the results of this research show that the "supportive" leadership style has a strong positive correlation with job satisfaction, in addition the "supportive" leadership style has a positive correlation with motivation. Job satisfaction increases through a good "supportive" leadership style, balanced with positive work motivation and teacher performance.